Healthcare-seeking of medical students: the effect of socio-demographic factors, health behaviour and health status - a cross-sectional study in Hungary - Afriza Umami; Viktória Zsiros; Ágnes Maróti-Nagy; Zsuzsanna Máté; Sudalhar Sudalhar; Regina Molnár; Edit Paulik (BMC, 2023)
Abstract Background Medical students are more likely to have various physical and psychological issues, but less information is available about the healthcare-seeking behaviour for physical and mental health issues. The aim of this study is to determine the factors affecting medical students' healthcare-seeking when visiting a general practitioner (GP) and/or psychologist. Methods 688 medical students (326 International and 362 Hungarian,) participated in a cross-sectional study. The information was gathered using a self-administered online questionnaire and covered socio-demographic background, health behaviour, general and mental health status and healthcare-seeking. For analysing adjusted associations, multivariable logistic regression models were used. Results Overall, 56.8% of medical students visit the GP; and 17.2%, the psychologist. Hungarian medical students visited the GP with chronic diseases, International medical students were more likely to visit a GP when they encountered sexual activity and had chronic diseases. Moreover, there was a significant correlation between sex, alcohol consumption, and perceived stress in the total sample of psychologist visits. When Hungarian medical students were in their clinical years and had a poor self-rated mental health, they were more likely to visit a psychologist. Whereas female international medical students and those who had poor self-rated mental health were more likely to seek psychological help. Conclusion Students visit a GP and/or psychologist is associated with a variety of factors, including socio-demographic background, health behaviours, and health issues. Medical schools should encourage help-seeking behaviours and early disclosure of medical students. Their ability to grasp healthcare attitudes and designing treatments will be important for both their academic success and future profession.